Mini Review: Risk Assessment, Clinical Manifestation, Prediction, and Prognosis of Mucormycosis: Implications for Pathogen- and Human-Derived Biomarkers - Acosta-España, Jaime David; Voigt, Kerstin (Frontiers in Microbiology, 2022)
Mucormycosis is a fungal disease caused by members of the fungal order Mucorales which are abundantly found in terrestrial environments. The fungi propagate clonally via mitospores which are transmitted to humans through the air and cause superficial or invasive infections. The disease has emerged in recent years and coincides generally with immunosuppression on the patient side. Mucormycosis is still rarely recognized in the clinical because of its unspecific symptoms which often triggers misdiagnosis with bacterial or viral infections leading to prolonged therapeutic cycles and loss of valuable time to manage mucormycosis properly. Infected patients develop various clinical forms, most notably ranging from rhinocerebral via pulmonary to gastrointestinal forms. Traditional diagnosis is based on culture and histopathologic examinations of the affected tissue. But, the achievement of a precise result is time-consuming, labor-intensive, requires mycological expertise and the finding appears often too late. A rapid and precise diagnosis is mandatory because symptoms are nonspecific and the disease is rapidly progressing with often fatal outcome. Mucormycosis was increasingly associated with other infections and underlying conditions and risk factors causing comorbitidies which are difficult to successfully manage. This mini-review summarizes the current knowledge on the epidemiology and causative agents of mucormycosis, transmission, risk factors, clinical presentation, diagnosis, and highlights the lack of appropriate biomarkers on the pathogen and host sides for rapid pathogen and host susceptibility detection, respectively. Fungal antigens and single nucleotide polymorphisms (SNPs) in human host genes are useful for the assessment of susceptibility.